The complete plastome sequence of a subtropical tree Pyrus betulaefolia (Rosaceae) - Dong, Zhanghong (Mitochondrial DNA B Resour, 2020)
The genus Pyrus, comprising several popular fruit crops worldwide, includes over 30 tree species. Here we determined the complete plastid genome sequence of Pyrus betulaefolia. The plastome consists of 160,184 bp, including a pair of inverted repeats (IRs) with a length of 26,384 bp separated by a large single-copy region (LSC) and a small single-copy region (SSC) of 88,121 bp and 19,295 bp, respectively. Further phylogenetic analyze was conducted using 11 complete plastid genomes of Rosaceae with KVM + F + I model, which supports Pyrus betulaefolia as a sister to all other eight Pyrus taxa with published plastomes.